Suberoylanilide hydroxamic acid, a novel histone deacetylase inhibitor, improves the development and acetylation level of miniature porcine handmade cloning embryos. (22nd April 2017) - Sun, JM; Cui, KQ; Li, ZP; Lu, XR; Xu, ZF; Liu, QY; Huang, B; Shi, DS
Contents: Histone deacetylase inhibitors (HDACis) can change the histone acetylation and significantly enhance the developmental competence of the pre‐implantation SCNT embryo. To select a proper histone deacetylase inhibitor to improve the success rate and potentially developmental ability of handmade cloning (HMC) embryos of miniature porcine, we compared the effect of two histone deacetylase inhibitors (SAHA vs. VPA) on HMC embryo development, their histone acetylation level and the expression level of relevant genes. The blastocyst rate and number of blastocyst cells of HMC embryos treated with SAHA (SAHA‐HMC) or VPA (VPA‐HMC) were significantly higher than those of control (Control‐HMC), respectively, but there were no significant difference between SAHA‐HMC and VPA‐HMC groups. In addition, the acetylation level (AcH4K8) of Control‐HMC and VPA‐HMC embryos at the blastocyst stage, respectively, was significantly lower than that of in vitro fertilized (IVF) and SAHA‐HMC embryos. However, the acetylation H4K8 of the blastocysts had no significant difference between SAHA‐HMC and the IVF groups. The SAHA‐HMC blastocysts indicated comparative expression levels of Oct4 and HDAC1 (histone deacetyltransferase gene) with those of IVF blastocysts. In contrast, the expression levels of Oct4 were lower and those of HDAC1 were higher in the VPA‐HMC and Control‐HMC blastocysts, respectively, compared to those of the IVF blastocysts. Our results demonstrated that the HMC embryos treated by SAHA could promote the pre‐implantation development and increase the levels of histone H4K8 acetylation and the expression of the OCT4 gene, yet decrease the expression of the HDAC1 gene to the comparable level of the IVF embryos. Our results proved that SAHA may be a better histone deacetylase inhibitor for porcine HMC compared to VPA, and furthermore, it may indicate that SAHA can effectively correct the abnormal histone acetylation during the HMC embryo development and subsequently improve the full‐term developmental potential of the HMC embryos after embryo transplantation.